CHCHD10 mutations promote loss of mitochondrial cristae junctions with impaired mitochondrial genome maintenance and inhibition of apoptosis. Issue 1 (14th December 2015) - Genin, Emmanuelle C; Plutino, Morgane; Bannwarth, Sylvie; Villa, Elodie; Cisneros‐Barroso, Eugenia; Roy, Madhuparna; Ortega‐Vila, Bernardo; Fragaki, Konstantina; Lespinasse, Françoise; Pinero‐Martos, Estefania; Augé, Gaëlle; Moore, David; et al.
Abstract: CHCHD10 ‐related diseases include mitochondrial DNA instability disorder, frontotemporal dementia‐amyotrophic lateral sclerosis (FTD‐ALS) clinical spectrum, late‐onset spinal motor neuropathy (SMAJ), and Charcot–Marie–Tooth disease type 2 (CMT2). Here, we show that CHCHD10 resides with mitofilin, CHCHD3 and CHCHD6 within the "mitochondrial contact site and cristae organizing system" (MICOS) complex. CHCHD10 mutations lead to MICOS complex disassembly and loss of mitochondrial cristae with a decrease in nucleoid number and nucleoid disorganization. Repair of the mitochondrial genome after oxidative stress is impaired in CHCHD10 mutant fibroblasts and this likely explains the accumulation of deleted mtDNA molecules in patient muscle. CHCHD10 mutant fibroblasts are not defective in the delivery of mitochondria to lysosomes suggesting that impaired mitophagy does not contribute to mtDNA instability. Interestingly, the expression of CHCHD10 mutant alleles inhibits apoptosis by preventing cytochrome c release. Synopsis: CHCHD10 is found to be part of the MICOS complex. Mutations in CHCHD10, previously associated with ALS, cause MICOS disassembly, loss of mitochondrial cristae, mitochondrial genome repair impairment after oxidative stress, and inhibition of apoptosis. CHCHD10 is found to be a component of the MICOS complex. CHCHD10 mutations disassemble the MICOS complex leading to loss of mitochondrial cristae junctions. Assembly of OXPHOS complexes is impaired leading to respiratory chain deficiency. Nucleoids are disorganized resulting in mtDNA repair impairment after oxidative stress. CHCHD10 mutations do not affect mitophagy. Expression of CHCHD10 mutant alleles prevents cytochrome c release and thus inhibits apoptosis via the caspase‐dependent pathway. Abstract : CHCHD10 is found to be part of the MICOS complex. Mutations in CHCHD10, previously associated with ALS, cause MICOS disassembly, loss of mitochondrial cristae, mitochondrial genome repair impairment after oxidative stress, and inhibition of apoptosis.